1999
DOI: 10.1247/csf.24.345
|View full text |Cite
|
Sign up to set email alerts
|

Stathmin and its Phosphoprotein Family. General Properties, Biochemical and Functional Interaction with Tubulin.

Abstract: Stathmin, also referred to as Op18, is a ubiquitous cytosolic phosphoprotein, proposed to be a small regulatory protein and a relay integrating diverse intracellular signaling pathways involved in the control of cell proliferation, differentiation and activities. It interacts with several putative downstream target and/or partner proteins. One major action of stathmin is to interfere with microtubule dynamics, by inhibiting the formation of microtubules and/or favoring their depolymerization. Stathmin (S) inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
165
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(174 citation statements)
references
References 79 publications
9
165
0
Order By: Relevance
“…This is consistent with the previous work that has shown that stathmin Ϫ/Ϫ mice are deficient in amygdala-dependent innate and learned fear, but are normal in hippocampus-dependent spatial memory (13). At the cellular level, stathmin is a negative regulator of microtubule formation (25) and in the amygdala of stathmin Ϫ/Ϫ mice a decrease in microtubule dynamics leads to deficits in synaptic plasticity (13), suggesting that the deficiency at the BLA synapses may be responsible for effects described here.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with the previous work that has shown that stathmin Ϫ/Ϫ mice are deficient in amygdala-dependent innate and learned fear, but are normal in hippocampus-dependent spatial memory (13). At the cellular level, stathmin is a negative regulator of microtubule formation (25) and in the amygdala of stathmin Ϫ/Ϫ mice a decrease in microtubule dynamics leads to deficits in synaptic plasticity (13), suggesting that the deficiency at the BLA synapses may be responsible for effects described here.…”
Section: Discussionsupporting
confidence: 93%
“…Stathmin family phosphoproteins including stathmin, SCG10, SCLIP, and RB3, have been proposed to play specific and complementary roles in the formation and maturation of the nervous system (Ozon et al, 1997(Ozon et al, , 1998Curmi et al, 1999). They have been originally identified for their capacity to integrate and relay intracellular signaling pathways (Sobel, 1991), at least in part through tubulin binding and the control of microtubule dynamics (Belmont and Mitchison, 1996;Curmi et al, 1997;Steinmetz et al, 2000;Charbaut et al, 2001;Ravelli et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It is highly conserved among vertebrates and is associated with tubulin binding and microtubule destabilization. 1,2 Stathmin-1 has a complex phosphorylation pattern in response to various extracellular signals, in particular growth and differentiation factors. 3 Moreover, stathmin-1 phosphorylation varies during the cell cycle.…”
mentioning
confidence: 99%